The practice of integrated healthcare and the experiences of people in Ghana's Ashanti region - Irene G. Ampomah; Bunmi S. Malau-Aduli; Abdul-Aziz Seidu; Aduli E. O. Malau-Aduli; Theophilus I. Emeto (BMC, 2022)
Abstract Background The Ghanaian government has implemented interventions that integrate traditional medicine (TM) into its national health system in response to the high prevalence of TM use. However, empirical evidence of the experiences of service users and the practice of integrated health in Ghana is scanty. Therefore, this study explored the experiences of people with TM integration into the formal health system in Ashanti region using an adapted TM integration framework. Methods A sequential explanatory mixed methods study design comprising survey administration and in-depth interviews for data collection was utilised to address the research objective. Framework analysis was used in analysing the qualitative data and for triangulation of results. Results Participants were aware of licensing and training of TM practitioners in a science-based university in Ghana. However, knowledge of the existence of TM units in selected hospitals in the region was minimal. Integration knowledge was largely influenced by sex, marital status, household size and residential status, where males and urban dwellers were more familiar with the process than females and rural dwellers. Low patronage of integrated health services in the region was attributable to weak cross referrals. However, service users who had engaged with the integrated system recounted a satisfactory outcome. Conclusion Service users' unfamiliarity with the presence of integrated facilities in Ghana could be an impediment to the practice of integrated healthcare. Sensitisation of the public about the practice of an integrated system could refine the Ghanaian integrated system. Regular evaluation of patient satisfaction and outcome measures might also serve as an effective strategy for improving health services delivery since evaluation is becoming an important component of health service design and implementation. There is the need for future studies to focus on exploring the perceptions and experiences of health practitioners and hospital administrators regarding the practice of integrated health in Ghana.